Pengujian Nilai LHV Bahan Bakar Bio Ethanol Tebu dan Pertalite Dengan Menggunakan Data Aquisisi Micro Kontroller Admel 2560 - Y Amanda; D Aswan; F A Kurniawan (Jurnal MESIL (Mesin Elektro Sipil), 2021)
Heat is defined as the heat energy possessed by a substance. In general, to detect the presence of heat possessed by an object that is by measuring the temperature of the object. Measurement of the amount of heat of reaction absorbed or released in a chemical reaction by experiment is called calorimetry. While the tool used to measure the amount of heat or calorific value released is a calorimeter. There are two types of calorimeters, namely bomb calorimeters and solution calorimeters. Bomb calorimeter serves as a tool to measure the number of calories or the calorific value of fuels such as bio ethanol and pertalite. The bomb calorimeter was then developed in a simple manner while still showing the function of the device. The stages carried out are defining, designing and developing using the admei 2560 micro controller. The research was carried out at the machine testing laboratory, Universitas Harapan Medan. In testing the calorific value of the fuel, the results of the LHV value for pertalite fuel are higher than for bio ethanol fuel. Meanwhile, the test results of the micro controller on the bomb calorimeter showed that the micro controller was effectively used in testing the calorific value calculation. The LHV value of each specimen of pertalite fuel and sugarcane bio ethanol fuel that the LHV value of pertalite fuel got the highest value compared to sugarcane bio ethanol fuel with a value of 8,501 Cal?kg, and for the LHV value of sugarcane bio ethanol got a value of 7, 33 Cal?kg.